Architettura e Illuminismo Filosofia e progetti di città nel tardo Settecento francese - Brancasi, Irene (Premio Tesi di Dottorato, 2014)
Her work analyses some modes of urban representation in the French culture of the second half of the eighteenth century. Two types of intellectual operations, description of reality and imagination of a better alterity, are combined to give voice to an increasingly lively critique of eighteenth-century cities, between reformist momentum and utopian spirit. The focus of the work is on the properly architectural urban representation, which was explored by Étienne-Louis Boullée (1728-1799) and Claude-Nicolas Ledoux (1736-1806). Their writings are unique contributions of a specific kind of Enlightenment and give shape to city models created by the union of architectural reform and transformation of the community.